POTENTIAL ADMINISTRATION OF LIPOIC ACID AND COENZYME Q AGAINST ADIPOGENSIS: TARGET FOR WEIGHT REDUCTION - AL-Ghamdi, Maryam A.; Choudhry, Hani; AL-Doghather, Huda A.; Huwait, Etimad H.; Kumosani, Taha A.; Moselhy, Said S (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Body overweight and obesity were considered as a risk factor for many systemic diseases as diabetichypertension, cardiovascular diseases, and some cancers. The lipoic acid and Co Q are considered as coenzymesneeded for enhancement metabolic rate. The goal of this study is to evaluate the anti-obese effect of lipoic acid alone orcombined with Co-Q in rats.Materials and Methods: Ninety male albino rats (100–150g) were used in this study, divided into six groups (15each). Group I: Normal rats fed normal diet. Group II: Rats fed high fat diet (HFD). Group III: Rats fed HFD weregiven lipoic acid (10 μg/kg b w /day) intra-gastric by stomach tube. Group IV: Rats fed HFD were given Co-Q (10 μg/kg b.w/day) intra-gastric. Group V: Rats fed HFD were given lipoic acid (50 mg/kg b w /day) and Co-Q (10 μg /kg b.w/day). Group VI: Rats were given orlistat intra-gastric (10 mg/kg b w/day) as positive control for 6 weeks. Serum wassubjected for determination of lipid profile, liver function tests atherogenic factor and lipoprotein lipase.Results: It was found that treatment with lipoic acid or Co-Q or combined showed increase in the activity oflipoprotein lipase (